﻿Ex situ population of the Harpy Eagle and its potential for integrated conservation - Marcos José de Oliveira; Francisca Helena Aguiar-Silva; Wanderlei de Moraes; Tânia Margarete Sanaiotti; Aureo Banhos; Nei Moreira (ZooKeys, 2022)
A main priority in conservation is the protection of species in their natural habitat. However, ex situ management of threatened species is a recognised strategy of conservation. Harpy Eagles (Harpia harpyja) are removed from the wild due to illegal capture, nest tree destruction, or other conflict sources. This study presents a review of the current ex situ Harpy Eagle populations in Brazil and worldwide, including information on the origin, sex, and year of entrance or year of birth under human care. Worldwide, until 2020 there were 205 Harpy Eagles in 77 different facilities in 16 countries, with 40 institutions in Brazil and 37 in other countries. The largest ex situ Harpy Eagle population is maintained in Brazil, with 139 individuals (75 females and 64 males) in 40 institutions. Of these institutions, there were 24 zoos, seven conservation breeding centres, six commercial breeders, two wildlife shelters, and one wildlife sorting centre. In Brazil, 62% (n = 86) of the individuals were hatched in the wild and 38% (n = 53) were bred in captivity under human care; for the wild individuals, only 73% (n = 64) have a known state of origin, with the majority from Pará state. This investigation provided relevant information to establish an ex situ demographic database. These individuals may potentially constitute a genetically and demographically viable safety population for future conservation strategies, as well as a source for research and education applied to Harpy Eagle integrated conservation.